3x+5=2(x-5)-x

Simple and best practice solution for 3x+5=2(x-5)-x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+5=2(x-5)-x equation:


Simplifying
3x + 5 = 2(x + -5) + -1x

Reorder the terms:
5 + 3x = 2(x + -5) + -1x

Reorder the terms:
5 + 3x = 2(-5 + x) + -1x
5 + 3x = (-5 * 2 + x * 2) + -1x
5 + 3x = (-10 + 2x) + -1x

Combine like terms: 2x + -1x = 1x
5 + 3x = -10 + 1x

Solving
5 + 3x = -10 + 1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
5 + 3x + -1x = -10 + 1x + -1x

Combine like terms: 3x + -1x = 2x
5 + 2x = -10 + 1x + -1x

Combine like terms: 1x + -1x = 0
5 + 2x = -10 + 0
5 + 2x = -10

Add '-5' to each side of the equation.
5 + -5 + 2x = -10 + -5

Combine like terms: 5 + -5 = 0
0 + 2x = -10 + -5
2x = -10 + -5

Combine like terms: -10 + -5 = -15
2x = -15

Divide each side by '2'.
x = -7.5

Simplifying
x = -7.5

See similar equations:

| f(2)=7x+8 | | 2(x+4)=6x+8 | | 3x+47=122 | | X-0.1X=13 | | -5x+6(x-4)=-16 | | -1/6-(5/8) | | 6(2x-3)-4x+2=4(2x+1)-5 | | -1/8-(5/6) | | 2x^3-27=0 | | 7x-8=x+12 | | 7y-12=6 | | 144=x*4x | | 144=x*2x | | 2n^2-9n+0=0 | | 8c+5=2(4c-8) | | 4y*y=3 | | 5y+10=45 | | -(-m+4m)=-6 | | 2n^2-9n+2=-2 | | 2n^2-9n+2=2 | | x+1=3k-1 | | 2x+1y=3.00 | | 2n^2-9n+2=0 | | 0=3/4x-3 | | 2.88x=9.12 | | 57w=450x | | 9x+3+2x=36 | | K/13=-28 | | 2+3x=-8+5 | | 12-2.88= | | 2x-14=62 | | 7-^3/2 |

Equations solver categories